The Upper Ordovician Pagoda positive δ13C excursion (PPCE) on the Upper Yangtze Platform, South China. (December 2022) - Ma, Xueying; Ogg, James; Lu, Yuanzheng; Fan, Ru; Huang, Chunju; Luo, Zhong; Deng, Shenghui
Highlights: First documentation of the Pagoda Positive Carbon Excursion (PPCE) on Upper Yangtze Platform. Astronomical tuning of 3 sections yielded similar PPCE durations of 4.0 ± 0.3 Myr. PPCE is coeval with regional transgression-highstand and oscillating climate. Abstract: The continuous and well exposed sections of the Upper Ordovician on the Upper Yangtze Platform were surveyed and sampled for δ 13 C and δ 18 O isotope and conodont fossils. The geochem-stratigraphic work in the Pagoda Formation has resulted in the recognition of a positive δ 13 C excursion, the Pagoda Positive δ 13 C Excursion (PPCE). The PPCE is a distinctive positive excursion occurring in the Middle-Late Katian, consists of three minor excursions ranging from 1.5 ‰ to 3 ‰, which has been identified in all the study sections on the Upper Yangtze Platform. The PPCE interval ranges through the conodont Hamarodus brevirameus and Protopandeordus inscrulptus conodont zones in ascending order, which indicates that the PPCE develops in the Middle-Late Katian of the Late Ordovician, while the Guttenberg δ 13 C Excursion (GICE) in the Baltoscandia and America extended from the Late Sandbian to the Early Katian. Spectral analysis of high-resolution magnetic susceptibility (MS) logs for the four study sections shows consistent wavelengths of ca. 2.0, 0.5, 0.18 and 0.15 m. The outcrop depth-series were tuned using 405-kyr long-eccentricity cycles and the astronomical tuning yields the duration of 3.7 to 4.4 myr for the PPCE event in different sections. This is the first documentation of the PPCE event on the Upper Yangtze Platform according to the geochemo-bio-cyclostratigraphy evidences, being identified within all portions of this platform in South China. It revised the previous description of the positive δ 13 C excursion of the Pagoda Formation on the Upper Yangtze Platform. The trigger of the PPCE was also briefly discussed in this paper.